Fused deposition modeling of novel scaffold architectures for tissue engineering applications - Zeina, I.; Hutmacherb, D.W.; Tanc, K.C.; Teoh, S.H.
Fused deposition modeling, a rapid prototyping technology, was used to produce novel scaffolds with honeycomb-like pattern, fully interconnected channel network, and controllable porosity and channel size. A bioresorbable polymer poly(e-caprolactone)(PCL)was developed as a filament modeling material to produce porous scaffolds, made of layers of directionally aligned microfilaments, using this computer-controlled extrusion and deposition process. The PCL scaffolds were produced with a range of channel size 160-700 mm, filament diameter 260-370 mm and porosity 48-77
Keywords: TISSUE ENGINEERING; SCAFFOLD; FUSED DEPOSITION MODELING; BIORESORBABLE POLYMER; POROSITY; INTERCONNECTED CHANNEL NETWORK; COMPRESSIVE PROPERTIES